Blue phase liquid crystal microcapsules: confined 3D structure inducing fascinating properties. Issue 16 (4th April 2019) - Lin, Pengcheng; Wei, Zhan; Yan, Qi; Chen, Ying; Wu, Minghui; Xie, Jiajin; Zeng, Minxiang; Wang, Wei; Xu, Jinliang; Cheng, Zhengdong
Abstract : 3D Confined blue phase liquid crystal microcapsules exhibit a widened BP temperature range, thermotropic color library and reversible surface-switch mode. Abstract : Blue phase liquid crystals (BPLCs) self-assembling into soft cubic crystalline structures possess significant applications in the field of dynamic photoelectron spectroscopy. However, three scientific challenges limit their broader application, namely, the difficulty to form a free-standing structure due to fluidity, dependence on nanoparticles or polymer matrix to widen the BP temperature range, and high working voltages to reorientate the LCMs. Herein, we proposed a new concept of free-standing BPLC microcapsules (BPLCMs) prepared by microfluidic emulsification and interfacial polymerization. The temperature range of BPLCs could be widened by surface anchoring and physical confinement. The BPLCMs built a color library in the visible region in the thermal response process. Most importantly, the stable BPLCMs exhibited a reversible surface-switch mode driven by an electric field lower than 0.55 V μm −1, which was the lowest record for BPLCs. The BPLCMs demonstrate intriguing prospects in the fields of smart display and reversible sensors.